Peningkatan Hasil Belajar Siswa dalam Ipa-Biologi Melalui Penggunaan Kartu Indeks pada Siswa Kelas Ix Upt Smp Muhammadiyah Cece Kabupaten Enrekang - Misram Misram (Jurnal Syntax Transformation, 2023)
The use of index cards in class IX UPT SMP Muhammadiyah Cece, Enrekang Regency. This study aims to obtain information about the learning outcomes of Biology students of grade IX UPT SMP Muhammadiyah Cece, Enrekang Regency for the 2021/2022 academic year who are taught using learning media in the form of index cards. The formulation of the problem in this study is whether the use of index cards can improve student learning outcomes in biology science in class IX UPT SMP Muhammadiyah Cece, Enrekang Regency. The variables studied are the understanding of index cards and student Biology learning outcomes, using the type of classroom Action Research. The population in this study was all 25 students of Class IX UPT SMP Muhammadiyah Cece Kab. Enrekang. The research design used is as many as two cycles, each cycle consisting of planning, implementation, observation or observation, and reflection. The research instruments used in data collection are biology learning outcomes tests, student activity observation sheets and questionnaires about student responses. The data analysis techniques used are qualitative analysis and quantitative analysis. The results showed that there was an increase in the learning outcomes of Biology Science students who were taught using index cards. The average score of biology learning outcomes of grade IX students of UPT SMP Muhammadiyah Cece Kab. Enrekang in cycle I through evaluation tests was 60.6% and the average score in cycle II increased to 72.08%. While the completeness of student learning outcomes in cycle I was 52% and in cycle II increased to 88%. so the use of learning media in the form of index cards can improve the learning outcomes of Science-Biology students of grade IX UPT SMP Muhammadiyah Cece, Enrekang Regency.